AN ERROR ANALYSIS OF USING PUNCTUATION MADE BY STUDENTS IN DESCRIPTIVE TEXT AT THE SECOND YEAR STUDENTS OF SMPN 3 WERA IN ACADEMIC YEAR 2017/2018 - Sarif Husada; Hidayati Hidayati; Humaira Humaira (Universitas Muhammadiyah Mataram, 2018)
Abstract: Punctuation is set of mark used in writing to clarify the meaning and to separate the sentences, word and part of word. The using of punctuation is considered as the important aspect in productive writing skill. Therefore, it was important students to master it. The purpose of this study is to find out the students’ errors in using punctuation in descriptive text made by second year students of SMPN 3 Wera in academic year 2017/018. The subject of this study is students’ from second year in SMPN 3 Wera. The mixed method qualitative and quantitative used in this study. The study applied purposive sampling. The researcher took 21 students as a sample at a class. In collecting the data, this study used observation and writing test as the research instrument then followed by analyzing the data using formula. This study found that were two kinds of punctuation and two types of errors (period, comma, omission and addition) which classified, there are 42 errors that occurs made by the students which consist of 11 or 26% students made errors in period, 15 or 36% errors of comma, 4 or 10% errors of addition and 12 or 28% errors of omission. The dominant errors showed by the students in form of comma which 15 or 36% errors. Based on the result of this study, the researcher concluded that the students still made many errors in using punctuation